2018
DOI: 10.3389/fnagi.2018.00316
|View full text |Cite
|
Sign up to set email alerts
|

Increased Functional Brain Network Efficiency During Audiovisual Temporal Asynchrony Integration Task in Aging

Abstract: Audiovisual integration significantly changes over the lifespan, but age-related functional connectivity in audiovisual temporal asynchrony integration tasks remains underexplored. In the present study, electroencephalograms (EEGs) of 27 young adults (22–25 years) and 25 old adults (61–76 years) were recorded during an audiovisual temporal asynchrony integration task with seven conditions [auditory (A), visual (V), AV, A50V, A100V, V50A and V100A]. We calculated the phase lag index (PLI)-weighted connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 84 publications
4
31
0
Order By: Relevance
“…Investigations have illustrated that peripheral resolution declines with age (Anderson and Mcdowell, 1998); therefore, another possible reason for the conflicting conclusions might be the location of the stimuli presented. The delayed AVI effect in older adults compared to that of younger adults was consistent with the findings of numerous previous studies, such as Wu et al (2012), Ren et al (2016), and Wang et al (2017and Wang et al ( , 2018. Colonius et al proposed a "time-windowof-integration model," which proposing that the integration of audiovisual integration includes at least two serial stages: an early afferent stage of peripheral processing (first stage) and a compound stage of converging sub-processes (second stage) (Colonius and Diederich, 2004;Diederich et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Investigations have illustrated that peripheral resolution declines with age (Anderson and Mcdowell, 1998); therefore, another possible reason for the conflicting conclusions might be the location of the stimuli presented. The delayed AVI effect in older adults compared to that of younger adults was consistent with the findings of numerous previous studies, such as Wu et al (2012), Ren et al (2016), and Wang et al (2017and Wang et al ( , 2018. Colonius et al proposed a "time-windowof-integration model," which proposing that the integration of audiovisual integration includes at least two serial stages: an early afferent stage of peripheral processing (first stage) and a compound stage of converging sub-processes (second stage) (Colonius and Diederich, 2004;Diederich et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Their audio-visual spatiotemporal perceptual training experiment in healthy older adults showed robust malleability of the aging brain (Yang et al, 2018). Additionally, Wang et al examined aging adaption from the view of functional connectivity during AV processing in older adults using an AV discrimination task, and their results showed that older adults activated stronger connections than younger adults (Wang et al, 2017(Wang et al, , 2018. Furthermore, a similar shift adaptive mechanism during memory tasks in the aging brain has been found (Davis et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the present study, the decrement of multi-scale centrality in the somatomotor network may indicate motor dysfunction and further supports the theory that motor impairment could occur at an early stage of AD, or even precede the onset of the cognitive impairment for AD by a decade and longer (Albers et al, 2015). The previous study has detected an increased functional brain network efficiency during the audiovisual task in aging (Wang et al, 2018a), while there is a negative connection between within-network functional connectivity in the visual network and levels of SCD (Contreras et al, 2017). These results indicate visual network impairment beginning from SCD.…”
Section: Discussionmentioning
confidence: 95%
“…increased connectivity, and lower sensorimotor performance in older adults, impacting general functionality [11]. Although controversial findings exist, an increased interregional coupling has frequently been observed across imaging methods in older populations during task-free [65, 66] and task-related conditions [67, 68] supporting the hypothesis of age-related dedifferentiation. The question as to whether alterations in GABAergic transmission reflect the cause or the ‘cure’ (i.e.…”
Section: Discussionmentioning
confidence: 99%